Assessment of the maternal key micronutrient supply and its correlation with cord blood parameters in twin pregnancies - Zgliczynska, Magdalena; Ostrowska, Magdalena; Zebrowska, Kinga; Rzucidlo-Szymanska, Iga; Szymusik, Iwona; Kowalski, Konrad; Kosinska-Kaczynska, Katarzyna (Frontiers in Public Health, 2025)
Background: Multiple pregnancy constitutes a large metabolic expense. Therefore, so women with twin pregnancies and neonates born as twins might be at a risk for micronutrient deficiencies. Therefore, the aim of the study was to assess the supplementation used and supply with key micronutrients: iron, vitamin B12, folic acid and vitamin D in women with twin pregnancies and the correlations with cord blood indicators.Methods: Maternal and cord blood samples were collected from 51 patients with twin pregnancies and 102 newborns born from those pregnancies between October 2020 and September 2023. Ferritin, vitamin B12, folic acid and vitamin D metabolite concentrations were measured. Additionally, the patients completed a questionnaire regarding pre-and intragestational supplementation before and during pregnancy.Results: Iron, vitamin B12, and vitamin D deficiency were diagnosed in 20.8%, 13.7% and 12.5% of women with twin pregnancies, respectively. No maternal folate deficiency was identified. Positive weak to moderate correlations were demonstrated between the concentrations of all studied indicators in the maternal and cord blood were found.Pregestational folic acid and vitamin D supplementation was associated with higher cord blood levels of folic acid and 3-epi-25(OH)D3, respectively. 25(OH)D3 and total 25(OH)D concentrations were higher in newborns whose mothers had supplemented vitamin D during pregnancy.The problem of iron, vitamin B12 and vitamin D deficiencies in twin pregnancies is still presentvalid. Pre-and intragestational supplementation, as well as maternal micronutrient supply affect the cord blood composition inof twins.